Health determinants of adolescent criminalisation. (February 2020) - Hughes, Nathan; Ungar, Michael; Fagan, Abigail; Murray, Joseph; Atilola, Olayinka; Nichols, Kitty; Garcia, Joana; Kinner, Stuart
Summary: Several conditions related to health and development in adolescence can increase the risk that a young person will be exposed to the criminal justice system. Such determinants include neurodevelopmental disability, poor mental health, trauma, and experiences of maltreatment. Furthermore, the risk of exposure to the criminal justice system seems to be amplified by social marginalisation and inequality, such that young people are made susceptible to criminal behaviour and criminalisation by a combination of health difficulties and social disadvantages. This Review presents evidence on the health determinants of criminalisation among adolescents, providing a persuasive case for policy and practice reform, including for investment in approaches to prevent criminalisation on the basis of health and developmental difficulties, and to better address related needs once within a criminal justice system.